DDDR-06. NEUROFIBROMATOSIS TUMOR SUPPRESSORS COOPERATIVELY DRIVE TUMOR DE-DIFFERENTIATION AND MEK INHIBITOR RESISTANCE IN PERIPHERAL NERVOUS SYSTEM TUMORS. (14th November 2022) - Vasudevan, Harish; Payne, Emily; Delley, Cyrille; Sale, Matthew; Liu, S John; Lastella, Sydney; Lucas, Calixto-Hope; Eaton, Charlotte; Casey-Clyde, Tim; Magill, Stephen; Chen, William; Reddy, Alyssa; et al.
Abstract: Schwann cell derived tumors comprising schwannomas, neurofibromas, and malignant peripheral nerve sheath tumors (MPNSTs) are the most common cancers of the peripheral nervous system and often arise in patients with neurofibromatosis type-1 (NF-1) or type-2 (NF-2). NF-1 is caused by loss of NF1, a negative regulator of Ras signaling, and NF-2 is caused by loss of NF2, a pleiotropic tumor suppressor with numerous functions including inhibition of PAK signaling. However, whether functional interactions exist between the NF1 and NF2 tumor suppressors remain unclear. More broadly, there are currently no effective molecular therapies for patients with Schwann cell tumors beyond the MEK inhibitor selumetinib to treat neurofibromas in patients with NF-1. Here, we integrate DNA methylation profiling, whole exome sequencing, bulk and single-cell RNA sequencing, biochemistry, and pharmacology across human samples, cell lines, and mouse xenografts to identify cellular de-differentiation as a driver of malignant transformation and selumetinib resistance. Single nuclear RNA-sequencing of human neurofibromas (n = 3) or MPNSTs (n = 3) revealed a total of 13 cell types with increased proliferating, de-differentiated tumor cell populations in MPNST samples. Single cell RNA-sequencing of MPNST mouse xenografts revealed persistence of de-differentiated cell populations in selumetinib treated samples compared to vehicle control, suggesting cellular de-differentiation underlies treatment resistance. A genome-wide CRISPRi screen for mediators of selumetinib response in NF1 deficient neurofibroma cells revealed NF2 loss drives selumetinib resistance. Consistently, NF2 suppression in NF1 deficient neurofibroma cells caused Schwann cell de-differentiation and activation of PAK, a serine threonine kinase. Translationally, a small molecule PAK inhibitor in combination with selumetinib formed an effective therapy in mouse MPNST xenografts. In sum, we elucidate a paradigm of de-differentiation driving malignant transformation and treatment resistance in Schwann cell tumors, uncovering a functional link between the NF1 and NF2 tumor suppressors that sheds light on a novel therapeutic vulnerability.